2018
DOI: 10.1136/bmjopen-2017-018703
|View full text |Cite
|
Sign up to set email alerts
|

Association of socioeconomic status with financial burden of disease among elderly patients with cardiovascular disease: evidence from the China Health and Retirement Longitudinal Survey

Abstract: ObjectivesThe prevalence of cardiovascular diseases (CVD) within low-income and middle-income countries has reached epidemic proportions. However, the association between out-of-pocket (OOP) payment and socioeconomic status (SES) of patients with CVD is not well studied. We aimed to understand the financial burden among Chinese middle-aged and older patients with CVD, and whether there was an association with SES.SettingsA nationally representative survey—The China Health and Retirement Longitudinal Survey (CH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 27 publications
1
21
0
1
Order By: Relevance
“…In 2010, three basic medical insurances, NCMS, URBMI, and UEBMI, in China have achieved near-universal coverage [25]. Previous studies in China found that basic medical insurances, particularly NCMS and URBMI, provided relatively high reimbursement proportion for inpatient care, but limited coverage for outpatient care [26,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, three basic medical insurances, NCMS, URBMI, and UEBMI, in China have achieved near-universal coverage [25]. Previous studies in China found that basic medical insurances, particularly NCMS and URBMI, provided relatively high reimbursement proportion for inpatient care, but limited coverage for outpatient care [26,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…However, the study mainly focused on inhospital mortality as the outcome, assessing educational attainment as one of the predictors for inhospital mortality among patients with AMI 20. Another study explored the association between socioeconomic status and financial burden among Chinese patients with CVD, but it did not provide evidence of patients’ outcomes, thus we have no idea about the association between education and outcomes among patients with AMI in China 21…”
Section: Discussionmentioning
confidence: 99%
“…The household registration system in China directly affects the ability to obtain various medical bene ts. 41 In our paper, the hospitalized reimbursement ratio of MIUE with cardiovascular disease patients was 69.8%, while that of the NCMS was only 39.7%, accounting for only half of the MIUE. Urban residents are expected to have a greater awareness about their health and better access to health insurance (especially private health insurance) and hence are more likely to obtain health insurance.…”
Section: Discussionmentioning
confidence: 56%